(untitled) (Kinesiology, 2023)
Competitive anxiety is an important issue in sport psychology since it is capable of influencing athletes’ performance. This study aims to examine the role of emotion regulation and personality in explaining individual differences in competitive anxiety of athletes, considering their sex and sport modality. A total of 101 athletes (50.5% males), aged between 18 and 69 years (M = 26.22; SD = 0.99), were included in this cross-sectional study. They filled out self-report scales on emotion regulation, personality, and competitive anxiety. Multiple regressions were used to analyze the data. Results partially supported our hypotheses. While sex differences were found in competitive anxiety, with women experiencing higher cognitive and somatic anxiety and lower self-confidence in comparison to men, no differences were found according to sport modality. Additionally, cognitive reappraisal was significantly associated with self-confidence, whereas neuroticism and extroversion were significantly associated with competitive anxiety dimensions. Key words: emotion regulation, personality, competitive anxiety